Evaluation of Self-Assessed State of Health and Vitamin D Knowledge in Emirati and International Female Students in United Arab Emirates (UAE) - Abboud, Myriam; Rizk, Rana; Papandreou, Dimitrios; Hijazi, Rafiq; Al Emadi, Nada Edris; Waszak, Przemyslaw M. (Frontiers in Psychology, 2020)
Introduction: Globally, vitamin D deficiency is one of the most common deficiencies, affecting nearly half the world's population. The objective of this survey was to assess and compare the knowledge about vitamin D and the perceived state of health in Emirati and international tourist female students in Dubai, UAE. Methods: This is a cross-sectional study that took place in universities in Dubai, UAE. This survey consisted of 17 multiple choice questions. The first part of the survey assessed levels of supplementation, diet and UV exposure. Another section evaluated the participants’ self-assessed state of health regarding vitamin D testing, symptoms related to vitamin D deficiency and general welbeing. The collected data were statistically analyzed using SPSS statistics for windows version 26.0 (SPSS Inc., Chicago, IL). Statistical significance was set at P<0.05. Results: 105 respondents were Emiratis and 65 were international students. The average age was 21, with an average BMI 23.3. Almost one-third of each group reported using Vitamin D supplements once weekly. The majority of both groups reported rarely getting tanned. Almost all participants reported regular consumption of Vitamin-D rich foods. In both groups, more than half reported consuming milk and cheese regularly and up to one-third reported consuming fish in a regular manner. Although more than half of the students rated their health as good; more than two-thirds reported experiencing muscle pain; only half reported having their blood Vitamin D levels measured once; half reported experiencing problems with concentration and more than three-quarters reported experiencing bad mood in the past month. The prevalence of these symptoms was almost similar across different categories of vitamin D supplementation, tanning habits, dietary intake, or nationality. No statistically significant differences were noted between the 2 groups. Conclusion: more Emirati students were aware of the association between vitamin D and osteoporosis than International tourist students (40% vs. 21.9%, respectively; p<0.05). On the other hand, both groups had lower knowledge about the relationship between vitamin D deficiency and depression, Rheumatoid Arthritis and Hypertension, and the optimal vitamin D level; however, no statistically significant differences were noted regarding this knowledge of Emiratis and international students.